2022
DOI: 10.1371/journal.pone.0271194
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable supply chain partner selection and order allocation: A hybrid fuzzy PL-TODIM based MCGDM approach

Abstract: Sustainability, as a trend of social development and the embodiment of corporate social responsibility, has begun to receive more attention. To achieve this goal, sustainable supplier selection (SSS) and order allocation (OA) are seen as the crucial activities in corporate management. In the process of SSS, the psychological behavior of decision-makers (DMs) could play a critical role in the evaluation results. Therefore, introducing it into the decision-making process may lead to decision in line with the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…An epsilon is defined as the threshold of acceptable limit for each of the objective functions, and considering varying epsilon, the Pareto set is identified [95]. An improved ε-constraint method named Augmented ε-constraint (AUGMECON) was also used by Hasani [96] and Zhong et al [97]. AUGMECON is more effective than the traditional ε-constraint method.…”
Section: Multi-objective Optimization (Moo) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An epsilon is defined as the threshold of acceptable limit for each of the objective functions, and considering varying epsilon, the Pareto set is identified [95]. An improved ε-constraint method named Augmented ε-constraint (AUGMECON) was also used by Hasani [96] and Zhong et al [97]. AUGMECON is more effective than the traditional ε-constraint method.…”
Section: Multi-objective Optimization (Moo) Methodsmentioning
confidence: 99%
“…AUGMECON is more effective than the traditional ε-constraint method. It requires less computational time as it provides a weak Pareto-optimal solution [97]. It also allows the simultaneous minimization of two functions that have conflicting objectives [96].…”
Section: Multi-objective Optimization (Moo) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the fixed subsidy policy and ARC policy improve the level of farmers’ environmentally sustainable investment and increase the profits of farmers and companies. Zhong et al [ 55 ] constructed a fuzzy multi-objective optimization model to select suppliers of sustainable supply chains from three aspects: economy, environment and society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, Pang proposed the concept of probabilistic linguistic term set (PLTS), which considers DMs' preferences for different linguistic terms by assigning different probabilities to them [16]. The rationality and flexibility of PLTS have attracted increasing attention from scholars, who have studied PLTS from various perspectives, including its operational laws [17,18], integration with MAGDM [19,20], and applications of probabilistic linguistic preference relations [21][22][23], etc. In addition, PLTS has found wide applications in fields such as patients prioritization assessment [24], evaluation and selection of online learning platforms [25], and risk assessment of marine ranching equity financing [26].…”
Section: Introductionmentioning
confidence: 99%